Effect of In Situ Thermal Annealing on Structural, Optical, and Electrical Properties of CdS/CdTe Thin Film Solar Cells Fabricated by Pulsed Laser Deposition - Alaa Ayad Al-mebir; Paul Harrison; Ali Kadhim; Guanggen Zeng; Judy Wu (Advances in Condensed Matter Physics)
An in situ thermal annealing process (iTAP) has been introduced before the common ex situ cadmium chloride (CdCl2) annealing to improve crystal quality and morphology of the CdTe thin films after pulsed laser deposition of CdS/CdTe heterostructures. A strong correlation between the two annealing processes was observed, leading to a profound effect on the performance of CdS/CdTe thin film solar cells. Atomic force microscopy and Raman spectroscopy show that the iTAP in the optimal processing window produces considerable CdTe grain growth and improves the CdTe crystallinity, which results in significantly improved optoelectronic properties and quantum efficiency of the CdS/CdTe solar cells. A power conversion efficiency of up to 7.0% has been obtained on thin film CdS/CdTe solar cells of absorber thickness as small as 0.75 μm processed with the optimal iTAP at 450°C for 10–20 min. This result illustrates the importance of controlling microstructures of CdTe thin films and iTAP provides a viable approach to achieve such a control.